SAT0259 Dermatological Features of Kawasaki Disease: Data Extracted from The French Kawasaki Disease Cohort (KAWANET). (15th July 2016) - Specht, C.; Darce, M.; Brochard, K.; Lechevalier, P.; Launay, E.; Kone Paut, I.; Piram, M.; ,
Abstract : Background: Kawasaki disease (KD) is a systemic vasculitis of unknown origin affecting mainly young children. The diagnosis criteria for KD described by the American Heart Association (AHA) include fever accompanied by five criteria, which are mainly mucocutaneous. Objectives: Given the importance of dermatological manifestations in KD we aimed to describe their types and frequencies in a large French cohort of patients, and to analyze their possible association with coronary arteries abnormalities (CAAs). Methods: Patients with complete and incomplete KD according to the AHA criteria and included between May 2011 and March 2013 in the French national database for KD (Kawanet), were analyzed. Consents were obtained for all included patients. Mucocutaneous signs of the disease were described (modification of the extremities detailed on erythema, edema and/or desquamation, diffuse exanthema, seat erythema and perineal desquamation, erythema or induration at BCG inoculation site, bilateral non purulent conjunctivitis, cheilitis (dry lips), raspberry tongue, erythema of oral mucosa) and their association with coronary artery abnormalities studied by multivariate analysis Results: We analyzed 142 KD patients classified according to the AHA criteria. Their mean age was 2.9 years. One hundred and twenty four (87.3%) were complete KD and 18 (12.7%) were incomplete KD. Changes in lips and oral cavity were found in 132 children (93%), bilateral conjunctiva injection in 129 (92%), changes in extremities in 117 (82%), diffuse exanthema in 107 (79%), perinea involvement in 53 (41%), and erythema or induration at the site of previous BCG immunization in 10 vaccinated children (13%). This latest sign was significantly more frequent in patients less than 1 years than in older ones (36% vs 9% p=0.01). CAAs were detected in 25 patients with complete KD (22%) and in all patients with incomplete Kawasaki disease by definition. No significant associations were found between any type of mucocutaneous lesion and CAAs in this study. Conclusions: Our study has underlined the importance of mucocutaneous symptoms for the definition of KD, and as expected, using the AHA criteria, they were associated with the phenotype of complete KD. In patients <1 year, modification on the site of previous TB immunization was significantly more reported than in older patients and so could be considered a diagnostic criterion. In addition, modification on the site of previous TB immunization and seat involvement were major and frequent dermatological clues for the diagnosis. Even frequent, none of the cutaneous symptoms were related to KD prognosis. Two limitations were present in this study: (i) some data were entered retrospectively; (ii) some groups of comparison were small and could explain the absence of association between mucocutaneous lesions and CAAs. This study was supported by a grant from the APHP: PHRC2009 Disclosure of Interest: None declared